2018
DOI: 10.1103/physrevb.97.155123
|View full text |Cite
|
Sign up to set email alerts
|

Numerical renormalization group method for entanglement negativity at finite temperature

Abstract: We develop a numerical method to compute the negativity, an entanglement measure for mixed states, between the impurity and the bath in quantum impurity systems at finite temperature. We construct a thermal density matrix by using the numerical renormalization group (NRG), and evaluate the negativity by implementing the NRG approximation that reduces computational cost exponentially. We apply the method to the single-impurity Kondo model and the single-impurity Anderson model. In the Kondo model, the negativit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…In a real quantum system, the thermal robustness of multipartite quantum correlations is an important property for quantum information processing [63][64][65][66][67]. The thermal state under the equilibrium at a finite temperature T can be written as ρ(T ) = 1 Z e −βH in which Z = tr[exp(−βH)] is the partition function with H being the system Hamiltonian and β = 1/k B T (for simplicity, the Boltzmann constant is chosen to be k B = 1).…”
Section: Properties Of Multipartite Quantum Correlation At Finite Tem...mentioning
confidence: 99%
“…In a real quantum system, the thermal robustness of multipartite quantum correlations is an important property for quantum information processing [63][64][65][66][67]. The thermal state under the equilibrium at a finite temperature T can be written as ρ(T ) = 1 Z e −βH in which Z = tr[exp(−βH)] is the partition function with H being the system Hamiltonian and β = 1/k B T (for simplicity, the Boltzmann constant is chosen to be k B = 1).…”
Section: Properties Of Multipartite Quantum Correlation At Finite Tem...mentioning
confidence: 99%
“…For quantum many-body systems the logarithmic negativity has been studied extensively in the literature [28][29][30]33,34,45,[48][49][50][51] . In particular, it has been found that E N displays the same universal contributions at quantum critical points 12,38,39,52 , as does the entanglement entropy 13,36,38 .…”
Section: Logarithmic Negativitymentioning
confidence: 99%
“…While the tilt control by changing the detuning is the most common "electrical" method to control a qubit, it has been recently realized, in double-quantum-dot spin qubit systems, that varying the barrier between the two dots ("barrier control") [51][52][53] serves as a powerful alternative to other methods, having advantages in many ways [54][55][56][57]. In this paper, we apply the barrier control to a charge qubit encoded in a triple-quantum-dot system.…”
Section: Introductionmentioning
confidence: 99%